Design and Build Virtual Reality-Based Smart Tourism and Hospitality as an Immersive Learning Media in the Pre-Practicum Stage of the Tourism Diploma Program - Oktovian Permana Aji; Apidiana Wulan Khristanti; Estikowati Estikowati (Jurnal Penelitian, 2026)
The development of digital technology encourages changes in learning methods in vocational education, especially in the field of tourism and hospitality which focuses on practical competencies. However, pre-practicum learning is still dominated by conventional methods so that it is not able to provide a learning experience that resembles real working conditions. This research aims to design and develop a Virtual Reality (VR)-based Smart Tourism and Hospitality learning system as an immersive learning medium to increase student readiness before participating in practicum activities. The research uses a Research and Development (R&D) approach through the Software Development Life Cycle (SDLC) model with the Waterfall method which includes the stages of needs analysis, system design, implementation, testing, and implementation. Needs analysis was carried out through the dissemination of Questioners, interviews, and discussions with lecturers and laboratories of the Hospitality and Travel Study Program. The results of the study show that students need learning media that is able to realistically simulate the work environment of the Front Office Hotel and tour guide activities. The prototype developed integrates scenario-based simulation and decision-based learning approaches so that students gain learning experience before carrying out the practicum directly. The development of this system supports the implementation of the Smart Laboratory concept while strengthening digital transformation in tourism vocational education through increasing learning effectiveness, practicum efficiency, and student competency readiness.